Environmental decision as an obligatory element of road investments in the Republic of Poland - Biskup, Katarzyna Grażyna (Polish Yearbook of Environmental Law, 2020)
Analysis of the effective regulations on the territory of the Republic of Poland allows to assume that the requirements of environmental protection are one of the strategic requirements related to the implementation of road investments. In addition to technical knowledge, the investor must study the environmental protection regulations that arise directly from standard regulations. The aim of this article is to demonstrate the essence of the environmental resolution as an obligatory element in the implementation of road investments in Poland.